With sugar and without affection: Violence against women in the context of Covid-19 (Research, Society and Development, 2021)
This article aims at the theme of violence against women in the context of Covid-19 and sought to answer some questions about public policies to protect women against violence, especially how the applicability of these policies is being guaranteed by institutions in a moment of social isolation. In view of this questioning, we sought from a bibliographical research to understand how the network of protection of women is restructuring to ensure that this woman victim of violence has her rights protected. It was possible to highlight a movement on the part of protection groups, authorities and institutions to modernize and diversify the forms of access of this woman to services and protection devices, through the media, opening of new channels of denunciation, social networks and digital media. Thus, the pandemic provided a reinvention of this work, in order to guarantee the integrity of women, even in situations of social distance.